Manipulation of a ring-shaped beam via spatial self- and cross-phase modulation at lower intensity. Issue 14 (25th March 2019) - Cheng, Lin; Zhang, Zhaoyang; Zhang, Lei; Ma, Danmeng; Yang, Gaoguo; Dong, Tian; Zhang, Yanpeng
Abstract : We report a tunable ring-shaped diffraction pattern via either nonlinear spatial self- or cross-phase modulation caused by the EIT-like effect in rubidium atomic vapor. Abstract : We report a tunable ring-shaped diffraction pattern via either nonlinear spatial self- or cross-phase modulation caused by the EIT-like effect in rubidium atomic vapor. During the propagation of an input Gaussian-profile beam, its output wavefront exhibits a ring-shaped diffraction pattern. Furthermore, the spot center can be tuned from dark to bright by varying individual experimental parameters, such as power, frequency detuning, the polarization state of the incident beams and atomic temperature, which makes the nonlinear phase shift evolve beyond 2π. In particular, the input intensity can be as low as 500 W m −2 .